Biomechanical report for the IAAF World Indoor Championships 2018 pole vault men - Hanley, B.; Gravestock, H.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2019)
The men`s pole vault took place on the afternoon of Sunday 4th March. With no qualifying rounds preceding the final, a large field of 15 men took part. World Record holder Renaud Lavillenie won gold with his second attempt at 5.90 m, with Sam Kendricks winning silver on countback from Piotr Lisek. There were personal best performances at 5.80 m for Kurtis Marschall and Emmanouil Karalís, with all athletes clearing at least one height. This report focusses on the run-up and takeoff phases of the pole vault competition.